Removal of Copper and Cobalt from Textile Wastewater using Date Palm as Bioadsorbance and Implication to pH - MUHAMMAD DANIEL BIN SHARUM; Muhammad Amirul Amri Bin Anuar; Norazreen Binti Sharip (Multidisciplinary Applied Research and Innovation, 2023)
A lot of wastewater has been produced by factories and has been discharged wastewater into water sources that have great potential to disrupt the health of organisms such as humans, plants, animals, and most aquatic life. Therefore, this study is important in the effort to remove heavy metals from wastewater. The wastewater was tested using Inductively Coupled PlasmaOptical Emission Spectroscopy (ICP-OES) twice which is before and after filtration. The sample will be undergoing ICP-OES twice to calculate the percentage of the heavy metal removal. The percentage of heavy metals removal from this experiment is too small between 2.0% to 2.4%. Even though date palm (DP) was successfully changing pH value before and after treatment of wastewater which in this case was textile wastewater evidenced by the pH meter results. ICP-OES analysis results show the type of heavy metals content on the wastewater such as Copper (Cu) and also Cobalt (Co) confirmed the removal of heavy metals by using date palm as bio adsorbent was able to identify types of heavy metals content on the wastewater. In conclusion, dates are an effective natural ingredient to be used as a bio-absorbent for wastewater.